Expediency of Application of the Regional and Municipal (Communal) Wealth Indicators at the Generation of the Regional and Urban Development Strategies - Lyashenko, V.I.; Zhykhareva, Yu.I.; Vyshnevskyy, O.S. (Економічний вісник Донбасу, 2013)
In accord with the analysis of fulfillment of the active regional development strategies in regions of Ukraine the effectiveness of their realization is rather low. There is no correlation between the determined strategic purposes of the regional development. The diversity of targets, which are determined in the strategies, leads to the resource scattering and makes the adequate quality monitoring of these strategies fulfillment impossible. It is impossible to define whether the positive changes took place during the given period in the final conclusion. The analogical situation happens in the process of building the strategy of the local communities' development. Also, the absence of the evaluative composite indicator of the effective realization of the development strategies prevents from the interregional comparison of the social and economic development and the monitoring of the contribution of each region in the national social and economic development. Як свідчить аналіз виконання наявних регіональних стратегій розвитку регіонів України, ефективність їх реалізації є вкрай низькою. Між визначеними стратегічними цілями регіонального розвитку відсутнє взаємоузгодження та взаємозв’язок. Різноманіття цільових показників, визначених в стратегіях, призводить до розпилення ресурсів та унеможливлює проведення адекватного моніторингу якості виконання цих стратегій. У кінцевому підсумку неможливо визначити, чи мали місце позитивні зміни загалом протягом визначеного періоду. Аналогічне становище має місце під час стратегування розвитку місцевих громад. Відсутність комплексного показника оцінки ефективності реалізації регіональних стратегій розвитку перешкоджає міжрегіональному співставленню соціально-економічного розвитку та моніторингу внеску кожного регіону в національний соціально-економічний розвиток. Как свидетельствует анализ выполнения действующих региональных стратегий развития регионов Украины, эффективность их реализации является крайне низкой. Между определенными стратегическими целями регионального развития отсутствует взаимосвязь. Многообразие целевых показателей, определенных в стратегиях, приводит к распыленности ресурсов и делает невозможным проведение адекватного мониторинга качества выполнения этих стратегий. В конечном итоге невозможно определить, имели ли место позитивные изменения в целом в течение определенного периода. Аналогичное положение имеет место при стратегировании развитии местных сообществ. Отсутствие комплексного показателя оценки эффективности реализации региональных стратегий развития препятствует межрегиональному сопоставлению социально-экономического развития и мониторинга вклада каждого региона в национальное социально-экономическое развитие.